PEMIKIRAN POLITIK TURKI USMANI HINGGA MASA MODERN - Duriana Duriana (IAIN Ambon, 2019)
ABSTRACT This study discusses the ideas of Ottoman Turkey to modern times. The purpose of this study is to describe how Ottoman Ottoman thought in the development of thinking in politics. The issues to be answered in this research are: What is the background of the emergence of Umani Turkish government and Ottoman Ottoman political ideas. This research is literature research with qualitative-descriptive method with critical-pilosofis approach. The results of the study found that the background of the emergence of Ottoman Ottoman government stems from the repentance of Sultan Ala ad-Din II of Turkey Saljuk Rum Ertoghul who led the war troops against the Roman army and then won. With this victory, the Sultan Ala ad-Din rewarded the Erthogul army, an area bordering Byzantium. Then he built the land and extended his territory to Byzantium. Erthogul had a son named Usman who was born in 1258. It was Usman's name that was taken as the name of the Ottoman Empire. The Ottoman Turkish political thought included thoughts in the field of kemeliteran and government, the fields of science and culture, and the religious field. Key Words: Political Thinking, Ottoman Turkey, Caliphate, Erthogul, Jenissary.